'Never any resting on laurels': Maureen MacGlashan in conversation with Christine Jacobs. (December 2018) - MacGlashan, Maureen; Jacobs, Christine
Abstract : Maureen MacGlashan, diplomat, indexer and editor o f The Indexer for 14 years (2004–18), was the keynote speaker for the ISC/SCI annual conference in June 2018. During a conversation on stage with Christine Jacobs, she talked about her diplomatic experiences, indexing, and editorship. This is an edited version of a report in the ISC Bulletin.